Murder at Mallowan Hall - Cambridge, Colleen (Cambridge, Colleen. Phyllida Bright mystery., 2021)
The housekeeper for archaeologist Max Mallowan and his famous wife, Agatha Christie, former Army nurse Phyllida Bright is faced with murder and mayhem during a weekend party and assembles the household staff to find the killer among the Mallowan's guests.